Investigating the Influence of Surface Runoff and Human Activities on the Seasonal Characterization of Physicochemical Properties of the upper segment of Qua Iboe River Water, Niger Delta, Nigeria - U. E. Jonah; I. I. Akpan; E. S. Umoh (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate the influence of surface runoff and human activities on the seasonal characterization of physicochemical properties o of the upper segment of Qua Iboe River Water, Niger Delta, Nigeria, using the protocols described in standard methods for the examination of water and wastewater. The values of physicochemical parameters assessed in water samples gave the following ranges: Water Temperature (22.0-31.6 oC), Dissolved Oxygen (1.5-7.42 mg/L), Total Dissolved Solids (48.6-130.6 mg/L), Electrical Conductivity  (72.5-195.0 mg/L), Turbidity (5.14-48.0 NTU), Sulphate (42.8-158.3 mg/L), Nitrate (1.76-17.48 mg/L),Phosphate (1.85-17.95 mg/L), Biochemical Oxygen Demand (0.62-6.51 mg/L), Chloride (22.29-80.36 mg/L) and Total Suspended Solids (22.1-91.5 mg/L). The mean values of Dissolved Oxygen, Nitrate and Biochemical Oxygen Demand in wet season exceeded the standard limits while Turbidity, Phosphate and Total Suspended Solids in both seasons exceeded the standard limits. ANOVA at P < 0.05 reveals significant variation in some parameters between the seasons. The findings revealed that surface runoff and anthropogenic activities influence the concentrations of some parameters.